Recognition of the Armed Conflict in Peru: The Inclusion of International Humanitarian Law in the Final Report of the Truth and Reconciliation Commission - Salmón, Elizabeth (2004)
In the context of both international and non-international armed conflicts - as was the case in Peru - there is an obligation to apply humanitarian norms, regardless of the reasons that led to them. This means that no situation justifies the use of force in violation of the rules of international humanitarian law (IHL). This concept was echoed in the final report of the Truth and Reconciliation Commission (TRC). In this sense, and due to the characteristics of the conflict that kept Peru in turmoil from the 1980s to the 2000s, a set of rules and principles applicable to this type of case has been established. Among these rules, Article 3, common to the four Geneva Conventions, stands out. This article contains provisions that reflect fundamental humanitarian principles that seek to protect human dignity and are customary in nature. It concludes that the obligations imposed by IHL and common Article 3 must be respected by both subversive groups and state forces.